Comparison of intraocular pressure fluctuation and glaucoma progression rate between phakic and pseudophakic eyes in pseudoexfoliation glaucoma - Kang, Edward; Park, Ji-Hye; Yoo, Chungkwon; Kim, Yong Yeon (Scientific reports, 2024)
The management of patients with concurrent pseudoexfoliation glaucoma (PXG) and cataract is challenging given its worse prognosis compared to other glaucoma types and the increased risk associated with cataract surgery. In this retrospective study, we investigated the long-term outcomes of cataract surgery in patients with PXG. We enrolled patients with PXG who had undergone cataract surgery at least 2 years previously and compared them with mean deviation (MD) matched patients with phakic eyes. The results showed that both groups experienced a decrease in MD, with the group of pseudophakic eyes exhibiting a significantly higher rate of decline (−2.15 ± 2.66 dB/year vs. −0.86 ± 0.95 dB/year; P = 0.040). Similarly, there was a trend towards more rapid thinning of the retinal nerve fiber layer in the pseudophakic group (−2.92 ± 2.34 μm/year vs. −1.79 ± 1.71 μm/year; P = 0.074). No significant differences in the intraocular pressure parameters were observed between the two groups. Multivariate analysis revealed that pseudophakic lens status was significantly associated with a faster rate of MD decline in patients with PXG (regression coefficient, −1.391; P = 0.022). These findings underscore the importance of close monitoring of patients with pseudophakic PXG to effectively manage glaucoma progression.